Family history of breast cancer and risk of benign breast diseases: an integrative literature review - Schilling, Marla Presa Raulino; Silva, Ilce Ferreira da (Mastology, 2020)
Introduction: Some benign breast diseases (BBD) can determine an increased risk of developing breast cancer. Environmental factors related to lifestyle and family history of breast cancer may be associated with BBD development. However, the effect of family history of breast cancer on the risk of benign breast diseases is still unclear. Objective: To evaluate the association between family history of breast cancer and benign breast diseases. Methods: This is an integrative review that selected observational studies in different databases to analyze the association between BBD and family history of breast cancer, considering the different classification criteria for both benign diseases and family history. All studies were published between 1977 and 2016. A total of 13 studies were selected, among which ten are case-control and case-cohort studies; and three are cohort studies. Most studies received high or moderate quality classification according to the Newcastle-Ottawa assessment scale. Results: Family history of breast cancer was associated with the development of proliferative lesions and the presence of atypia, and it was more closely related to the development of benign diseases in young women, with a tendency to decrease with advancing age. Conclusion: Studies suggest there may be an association between family history of breast cancer and benign breast diseases; nevertheless, no statistically significant results were found in many case-control studies, and more robust prospective research is necessary to further clarify this association.